Coexistence of Straatsma syndrome without macular extension and abnormal ellipsoid zone - Eröz,Pinar (2022)
ABSTRACT Myelinated retinal nerve fibers are rare congenital anomalies that appear as gray-white patches. They may be present in a syndrome characterized by ipsilateral myelinated retinal nerve fibers, myopia and amblyopia. The author reported an ellipsoid zone defect on spectral domain optical coherence tomography in a case of Straatsma syndrome without macular extension.